The influence of integrated sustainability practices on the sustainability of halal businesses - Jaiyeoba, Haruna Babatunde; Abdullah, Moha Asri; Khalid, Azam Abdelhakeem (Emerald Publisher, 2025)
Purpose – Despite the emphasis on integrated sustainability practices, many businesses continue to pursue sustainability strategies focused solely on a bottom line that prioritises monetary profits, often neglecting other crucial aspects of sustainability, including social, environmental and philanthropic considerations. This research aims to investigate the significance of adopting integrated sustainability practices by examining whether these practices contribute to the sustainability of halal businesses from the perspective of halal consumers.